Mental health professionals as ‘silent frontline healthcare workers’: perspectives from three South Asian countries - Sheikh Shoib; Anoop Krishna Gupta; Waleed Ahmad; Shijo John Joseph; Samrat Singh Bhandari (Open Journal of Psychiatry and Allied Sciences, 2022)
Mental health professionals across the globe foresaw the mental health impact of the coronavirus disease 2019 (COVID-19) pandemic. They have faced scarcity of trained professionals, rising morbidities, lack of protective gear, shortage of psychotropic drugs, and poor rapport building due to masking and social distancing. Amidst all, they have responded with approaches that focus on continuing mental health services to the patients already in care, education of the vulnerable people to help them cope with these stressors, and provide counselling services to patients and families affected by the pandemic.